The twelve days of Christmas - Ray, Jane. (Somerville, Mass. : Candlewick Press, 2011)
On each of the twelve days of Christmas, more and more gifts arrive from the recipient's true love.
Keywords: Folk songs, English -- England -- Texts; Christmas music -- Texts